Assimilação do conceito de estequiometria a partir de uma unidade de ensino potencialmente significativa - UEPS - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
Meaningful learning is a theory of learning with a cognitive approach created by David Ausubel that seeks to understand how the acquisition and development of knowledge in human cognition occurs. Its major focus is on learning concepts and how they are formed and assimilated into the so-called subsunctions, a process in which new information interacts with a specific knowledge structure. Based on the Theory of Meaningful Learning, this work used as a method the Potentially Significant Teaching Units (PMTU) in order to respond as it happens to the assimilation of the concept of stoichiometry in students graduating in chemistry, having as principle the two pillars of Significant Learning: the material to be learned is potentially significant to the learner; The apprentice manifests a willingness to acquire new knowledge. The PMTU have as one of their principles to make use of diversified methodologies to make teaching more dynamic and efficient for students. With this, this research was based on the qualitative and technical approach of the action research, having as instrument of data collection, questionnaires, conceptual maps, problem situations, activity sheets among others with the objective of adequately following the transversal aspects of PMTU. The PMTU was applied with 12 volunteer participants, assuming that the student should want to learn, and performed during 14 meetings totaling 30 hours. The results obtained suggest that, when working with different methodologies that complement the purpose of promoting the assimilation of the stoichiometry concept, the students developed both the ability to work cooperatively and their criticality, important attitudinal aspects, as well as evidence to understand better the stoichiometry, where one can corroborate the assimilation of the concept from the answers obtained in the proposed activities. Finally, the use of PMTU during classes as a methodology is important because it employs diversified teaching strategies.
Keywords: Aprendizagem significativa; Licenciatura em química; Ensino-aprendizagem; CIÊNCIAS EXATAS E DA TERRA: QUÍMICA